Anodic Oxidation for the Stereoselective Synthesis of Heterocycles - Yamamoto, Kosuke; Kuriyama, Masami; Onomura, Osamu (Accounts of chemical research, 2020)
Conspectus Stereodefined aliphatic heterocycles are one of the fundamental structural motifs observed in natural products and biologically active compounds. Various strategies for the synthesis of these building blocks based on transition metal catalysis, organocatalysis, and noncatalytic conditions have been developed. Although electrosynthesis has also been utilized for the functionalization of aliphatic heterocycles, stereoselective transformations under electrochemical conditions are still a challenging field in electroorganic chemistry. This Account consists of four main topics related to our recent efforts on the diastereo- and/or enantioselective synthesis of aliphatic heterocycles, especially N-heterocycles, using anodic oxidations as key steps. The first topic is the development of stereoselective synthetic methods for multisubstituted piperidines and pyrrolidines from anodically prepared α-methoxy cyclic amines. Our strategies were based primarily on N-acyliminium ion chemistry, and the key electrochemical transformations were diastereoselective anodic methoxylation, diastereoselective arylation, and anodic deallylative methoxylation. Furthermore, we found a unique property of the N-cyano protecting group that enabled the electrochemical α-methoxylation of α-substituted cyclic amines. The second topic of investigation is memory of chirality in electrochemical decarboxylative methoxylation. We observed that the electrochemical decarboxylative methoxylation of oxazolidine and thiazolidine derivatives with the appropriate N-protecting group occurred in a stereospecific manner even though the reaction proceeded through an sp2 planar carbon center. Our findings demonstrated the first example of memory of chirality in N-acyliminium ion chemistry. The third topic is the synthesis of chiral azabicyclo-N-oxyls and their application to chiral organocatalysis in the electrochemical oxidative kinetic resolution of secondary alcohols. The final topic is stereoselective transformations utilizing anodically generated halogen cations. We investigated the oxidative kinetic resolution of amino alcohol derivatives using anodically generated bromo cations. We also developed an intramolecular C–C bond formation of keto amides, a diastereoselective bromoiminolactonization of α-allyl malonamides, and an oxidative ring expansion reaction of allyl alcohols. It is noteworthy that most of the electrochemical reactions were performed in undivided cells under constant-current conditions, which avoided a complicated reaction setup and was beneficial for a large-scale reaction. In addition, we developed some enantioselective electrochemical transformations that are still challenges in electroorganic chemistry. We hope that our research will contribute to the further development of diastereo- and/or enantioselective transformations and the construction of valuable heterocyclic compounds using an electrochemical approach.